2002
DOI: 10.1080/1061186021000054933
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Uptake of Pulmonary Delivered Radiolabelled Solid Lipid Nanoparticles

Abstract: Results indicate that SLN could be effective colloidal carriers for lymphoscintigraphy or therapy upon pulmonary delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(87 citation statements)
references
References 20 publications
0
86
0
Order By: Relevance
“…administered dose crossing the air-blood barrier within the first 25 min post-administration (Fig. 3B) and a majority of the signal accumulating in the kidneys and bladder [27,28], from where it was eliminated within 24 h (Fig. 3C-D).…”
Section: Lung Clearance and Biodistribution Using Non-invasive Longitmentioning
confidence: 99%
“…administered dose crossing the air-blood barrier within the first 25 min post-administration (Fig. 3B) and a majority of the signal accumulating in the kidneys and bladder [27,28], from where it was eliminated within 24 h (Fig. 3C-D).…”
Section: Lung Clearance and Biodistribution Using Non-invasive Longitmentioning
confidence: 99%
“…Deposition and clearance of SLNs were assessed by Videira and colleagues 133,134 after inhalation of aerosolized insoluble particles using gamma-scintigraphy imaging analysis. It was observed that a few minutes after deposition, inhaled material began to translocate to regional lymph nodes indicating that inhalation can be an effective route to deliver drug-containing lipid partices to the lymphatic systems and lipid particles can be used as potential drug carriers for lung cancer therapy, as well as for vaccine delivery.…”
Section: Dovepressmentioning
confidence: 99%
“…From these experiments, biodistribution of SLNs can be traced and evaluated. 133,134 Fluorescence/bioluminescence imaging systems for pulmonary gene delivery Visualization and evaluation of both the pulmonary delivery and the gene expression properties after dry powder inhalation in mice were recently reported by Mizuno and colleagues. 215 It was shown that the pulmonary delivery and Nanomedicine in pulmonary delivery Dovepress submit your manuscript | www.dovepress.com Dovepress the gene expression can be evaluated using fluorescence of indocyanine green (ICG) as a fluorescent label and the detection of luciferase activity, respectively, by using a nondestructive real-time in vivo imaging system.…”
Section: -214mentioning
confidence: 99%
“…Finally, it is possible to control the physical location of a lipophilic component and to slow down molecular diffusion processes using conventional emulsions by crystallizing the lipid phase. These systems are known as solid lipid particle emulsions, which consist of emulsifier coated (partially) solid lipid particles dispersed in an aqueous continuous phase ( Figure 5) (Videira et al, 2002). By controlling the morphology of the crystalline lipid matrix it is possible to obtain more precise control over the release kinetics of functional compounds.…”
Section: Fig 5 Examples Of Different Emulsions-based Delivery Systemsmentioning
confidence: 99%